2015
DOI: 10.5478/msl.2015.6.3.53
|View full text |Cite
|
Sign up to set email alerts
|

MS Platform for Erythropoietin Glycome Characterization

Abstract: Recombinant erythropoietins (EPOs) are an important class of biotherapeutics that stimulate red blood cell production. The quality, safety, and potency of EPO variants are determined largely by their glycosylation, which makes up nearly half their mass. Thus, detailed glycomic analyses are important to assess biotherapeutic quality and establish the equivalency of biosimilar EPOs now coming to market. High-resolution mass spectrometry (MS) has recently emerged as the premier tool for glycan analysis in EPOs. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…It has been shown that the glycan composition of the biopharmaceuticals is critically depending on the presence and activity of different glycosyltransferases, concentration of substrates, cell lines, and cell culture conditions, making the production of therapeutic glycoproteins challenging . EPO is highly heterogeneous with a variety of glycosylation patterns as well as post-glycosylational modifications, such as sialylation by N -acetylneuraminic acid (Neu5Ac) or N -glycolylneuraminic acid (Neu5Gc), phosphorylation, and O-acetylation . These patterns have a significant impact on the drug efficiency and adverse drug effects in EPO-treated patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the glycan composition of the biopharmaceuticals is critically depending on the presence and activity of different glycosyltransferases, concentration of substrates, cell lines, and cell culture conditions, making the production of therapeutic glycoproteins challenging . EPO is highly heterogeneous with a variety of glycosylation patterns as well as post-glycosylational modifications, such as sialylation by N -acetylneuraminic acid (Neu5Ac) or N -glycolylneuraminic acid (Neu5Gc), phosphorylation, and O-acetylation . These patterns have a significant impact on the drug efficiency and adverse drug effects in EPO-treated patients.…”
Section: Introductionmentioning
confidence: 99%
“… 5 EPO is highly heterogeneous with a variety of glycosylation patterns as well as post-glycosylational modifications, such as sialylation by N -acetylneuraminic acid (Neu5Ac) or N -glycolylneuraminic acid (Neu5Gc), phosphorylation, and O-acetylation. 6 These patterns have a significant impact on the drug efficiency and adverse drug effects in EPO-treated patients. As an example, increases of the Neu5Gc containing glycoproteins can lead to immunogenic or inflammatory responses in patients.…”
Section: Introductionmentioning
confidence: 99%
“…5 EPO is highly heterogeneous with a variety of potential glycosylation patterns as well as post-glycosylational modifications, such as sialylation by N-acetylneuraminic acid (Neu5Ac) or N-glycolylneuraminic acid (Neu5Gc), phosphorylation and O-acetylation. 6 These patterns have a significant impact on the drug efficiency and adverse drug effects in EPO-treated patients. As an example, increases of the Neu5Gc containing glycoproteins can lead to immunogenic or inflammatory responses in patients.…”
Section: Introductionmentioning
confidence: 99%